Optimization of Aeration for Accelerating Municipal Solid Waste Biodrying - Panida Payomthip; Sirintornthep Towprayoon; Chart Chiemchaisri; Suthum Patumsawad; Komsilp Wangyao (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
Biodrying technology is commonly used in Thailand to produce refuse-derived fuel (RDF), however, this technology remains ineffective on high-moisture waste. Air supply is key to ensuring homogenous temperature development within the waste matrix during biodrying, increasing RDF quality. This study investigated negative aeration during local municipal solid waste biodrying to meet RDF standards in reduced time. Lysimeter experiments were performed on pre-shredded waste (300 kg/m3) using different aeration patterns. The temperature, vent gas oxygen level, weight loss, and leachate volume during the biodrying process were monitored. In addition, the treated waste’s temperature, moisture, and heating values were evaluated to determine the biodrying process efficiency. The results indicate that shorter heating phases can be achieved during continuous aeration. No significant temperature variation was observed in the waste layers, with a low standard deviation of 1.96% during constant air supply, indicating homogeneous temperature development during the biodrying process. The vent gas contained 15–20% oxygen and non-detectable methane, evidencing sufficient air supply. The total heat development was independent of aeration pattern; therefore, biodrying was unaffected by excess air supply at a 95% confidence level. The highest weight loss and moisture content reduction were 25% and 66%, respectively. The optimal aeration was continuous mode with non-excessive aeration, increasing the lower heating value from 2,884.0 to 4,938.0 kCal/kg, and reducing the moisture content from 48.5% to 22.2%. RDF quality can be improved 1.7 times to meet Thailand’s standards within a short biodrying period of 7 days using homogeneous temperature distribution operated under continuous aeration